Design and Construction of an Automatic Door System Based on Iris Detection Using Esp32-Cam and OpenCV Using the Rapid Application Development (RAD) Method - Angelika, Nanda; Nurhasanah (LPPM Politeknik Aceh Selatan, 2026)
Conventional home security systems typically depend on mechanical keys and passive CCTV cameras, which do not offer active access control or real-time response. This study presents the design and implementation of an automatic door system that uses iris recognition for authentication, developed with an ESP32-S3 camera and OpenCV, and integrated into a Flutter-based mobile application. The system was created using the Rapid Application Development (RAD) method to ensure flexibility and fast iteration. The prototype includes biometric iris authentication, solenoid-based door locking, live video monitoring, alarm activation, and real-time notifications. Through black-box testing, the system achieved high recognition accuracy, maintained stable operation in low-light environments, and successfully prevented unauthorized access using photo or video spoofing. Additionally, users receive instant alerts for failed access attempts or suspicious motion. The results show that integrating iris biometrics with IoT technology significantly enhances both home security and user convenience. Compared to traditional locks and CCTV systems, this approach provides a more intelligent, responsive, and secure solution for modern smart homes, offering users greater safety, automation, and peace of mind.